2015
DOI: 10.1063/1.4917514
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism in Ti-doped ZnO thin films

Abstract: We report our study on the origin of ferromagnetism in Ti-doped ZnO. A series of Ti doped ZnO films with increasing concentration of Ti dopant were grown and characterized in terms of structural, electrical, and magnetic properties. We found that Ti has a low solubility in the ZnO wurtzite structure. This favors stabilization of a large number of Zn vacancies, and theoretical calculations have shown that they can carry substantial magnetic moment. A carrier mediated exchange interaction between Zn vacancies is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
4
11
0
Order By: Relevance
“…Consequently, if dopants would have substituted Zn 2+ into the lattice, a shift toward higher 2 θ angles would be expected. The shift toward lower angles was already reported for Ti doped ZnO and it was attributed to the presence of doping atoms (Ti) into interstitial sites, instead of substitutional sites . All dopants used in the current study have atomic radii larger than the atomic radius of Zn in the following order: Zr (206 pm) > W (193 pm) > Ti (176 pm) > Mn (161 pm) > Zn (135 pm).…”
Section: Resultssupporting
confidence: 77%
“…Consequently, if dopants would have substituted Zn 2+ into the lattice, a shift toward higher 2 θ angles would be expected. The shift toward lower angles was already reported for Ti doped ZnO and it was attributed to the presence of doping atoms (Ti) into interstitial sites, instead of substitutional sites . All dopants used in the current study have atomic radii larger than the atomic radius of Zn in the following order: Zr (206 pm) > W (193 pm) > Ti (176 pm) > Mn (161 pm) > Zn (135 pm).…”
Section: Resultssupporting
confidence: 77%
“…First, room‐temperature switchable magnetization in BF–BT:Zn is predominantly attributed to the isolated ZnO particles. Some of the Zn cations have entered into lattice to substitute B‐site Fe/Ti cations, therefore, some substituted Fe/Ti cations enter into the ZnO to form diluted magnetic materials of ZnO:Fe and/or ZnO:Ti, both show room‐temperature ferromagnetic behavior . Second, the origin for room‐temperature switchable magnetization of BF–BT:Cr includes the two factors.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the Zn cations have entered into lattice to substitute B-site Fe/Ti cations, therefore, some substituted Fe/Ti cations enter into the ZnO to form diluted magnetic materials of ZnO:Fe and/ or ZnO:Ti, both show room-temperature ferromagnetic behavior. 38,39,51 Second, the origin for room-temperature switchable magnetization of BF-BT:Cr includes the two factors. One is that the substituted Fe/Ti cations can enter into lattice of Cr 2 O 3 particles, leading to distorted Cr 2 O 3 , which generally enhance magnetic behavior.…”
Section: Resultsmentioning
confidence: 99%
“…In the case where foreign atoms are incorporated into interstitial sites and not as substitutional ions instead of Zn 2+ , a peak shi toward lower angles was reported. 11,27 Detailed studies performed on Aldoped ZnO demonstrated that Al is found in both substitutional and interstitial sites, 28,29 whereas Ti is found as interstitial. 27 The atomic radii of the dopants (206 pm for Zr, 193 pm for W, 176 pm for Ti and 161 pm for Mn) are all larger than that of Zn (135 pm), with the exception of Al (118 pm).…”
Section: Xrd-measurementsmentioning
confidence: 99%
“…11,27 Detailed studies performed on Aldoped ZnO demonstrated that Al is found in both substitutional and interstitial sites, 28,29 whereas Ti is found as interstitial. 27 The atomic radii of the dopants (206 pm for Zr, 193 pm for W, 176 pm for Ti and 161 pm for Mn) are all larger than that of Zn (135 pm), with the exception of Al (118 pm). Therefore, it can be inferred that Mn, Ti, Zr and W doping elements occupy interstitial positions in the ZnO matrix.…”
Section: Xrd-measurementsmentioning
confidence: 99%